Exploring the Italian equine gene pool via high-throughput genotyping - Capomaccio, Stefano; Ablondi, Michela; Colombi, Daniele; Sartori, Cristina; Giontella, Andrea; Cappelli, Katia; Mancin, Enrico; Asti, Vittoria; Mantovani, Roberto; Sabbioni, Alberto; Silvestrelli, Maurizio (Frontiers in Genetics, 2023)
The Italian peninsula is in the center of the Mediterranean area, and historically it has been a hub for numerous human populations, cultures, and also animal species that enriched the hosted biodiversity. Horses are no exception to this phenomenon, with the peculiarity that the gene pool has been impacted by warfare and subsequent “colonization”. In this study, using a comprehensive dataset for almost the entire Italian equine population, in addition to the most influential cosmopolitan breeds, we describe the current status of the modern Italian gene pool. The Italian dataset comprised 1308 individuals and 22 breeds genotyped at a 70 k density that was merged with publicly available data to facilitate comparison with the global equine diversity. After quality control and supervised subsampling to ensure consistency among breeds, the merged comparison with the global equine diversity contained data for 1333 individuals from 54 populations. Multidimensional scaling, admixture, gene flow, and effective population size were analyzed. The results show that some of the native Italian breeds preserve distinct gene pools, potentially because of adaptation to the different geographical contexts of the peninsula. Nevertheless, the comparison with international breeds highlights the presence of strong gene flow from renowned breeds into several Italian breeds, probably due to historical introgression. Coldblood breeds with stronger genetic identity were indeed well differentiated from warmblood breeds, which are highly admixed. Other breeds showed further peculiarities due to their breeding history. Finally, we observed some breeds that exist more on cultural, traditional, and geographical point of view than due to actual genetic distinctiveness.